Viralité : focus sur les motivations du partage - Ugo Roux (MediAzioni)
In the present work, we propose to uncover some of the motivations that lead to the sharing of content on the Internet. To this end, as part of our experimental protocol, we asked our subjects to declare the reasons that motivated them to share or not the videos from our corpus that were given to them for viewing. The textual data thus collected were subjected to various analyses. Our initial analyses show that humor is a major – indeed central – factor in viral dynamics.